Thyroid Gland Metastasis from Cancer of the Uterine Cervix: An Extremely Rare Case Report - Celik, Suleyman Utku; Besli, Dilara; Sak, Serpil Dizbay; Genc, Volkan (Acta medica (Hradec Kralove), 2016)
The thyroid gland is a relatively uncommon site for a metastatic disease, although it is richly supplied with blood. The metastases may originate from various primary sites, mainly kidney, lung, head and neck, and breast. Thyroid metastasis from cervical carcinomas is extremely rare; and only a few cases have been previously reported in the literature. In patient with thyroid nodules and an oncological history, the possibility of thyroid metastasis should be seriously considered. Despite the rarity of the metastasis of cervical carcinoma to the thyroid, it is difficult to say appropriate treatment approach for these lesions. When managing such patients, decision-making should balance the possibility of gaining long-term survival against estimation of the aggressiveness of the disease and its possible complications. Here, a case of thyroid metastasis from a squamous cell carcinoma of the uterine cervix presenting with cervical mass and difficulty in swallowing and its treatment is reported.
Keywords: nádory štítné žlázy; Thyroid gland; Uterine Cervical Neoplasms; Cancer of the uterine cervix; Carcinoma, Squamous Cell; Middle Aged; lidé středního věku; lidé; Female; Thyroid Neoplasms; Metastasis; spinocelulární karcinom; nádory děložního čípku; ženské pohlaví; Humans